ACCESS CONTROL AND ALERT SYSTEM - RAO, B.VENKATESWAR; RAJU, K.; ASMA, MD.; SANJANA, Y.; KIRAN, D.SAI (The journal of contemporary issues in business and government, 2021)
In this world, there is a need of security in pretty much every area for example structures, banks, homes, and so on the grounds that robberies are expanded by step by step. To conquer this danger a security framework has been proposed utilizing Arduino and IR Sensor. In this innovation, At the point when the client enters the right secret phrase then the two-way confirmation a randomly produced OTP is shipped off the client gadget. On the off chance that the OTP is coordinated, the framework will be opened. On the off chance that the OTP isn't right, the client will be furnished with just the set number of possibilities (for example three possibilities in the proposed framework). So, what we did is a computerized innovation to build a very much incorporated and altered security framework at a sensible cost.